SISTEM PENGGERAK GONDOLA DENGAN MENGGUNAKAN HANDPHONE - Susila, Tjandra; Setyaningsih, Endah; Soedjaya, Pranata (TESLA Jurnal Teknik Elektro UNTAR, 2008)
Gondola is a human technology used to clean the glass windows building facade. However, in many uses an accident victim who pluck the soul because of various factors, among other natural factors or human negligence itself Gondola that design is a "system of the Gondola Using Handphone" and equipped with wind sensors. It is expected that with the help of this tool make it easier for officers to clean the glass windows of buildings without climbing gondola, because this system is designed to work automatically to clean the glass window. This design uses many components, such as motor DC, microcontroller,power supply and many more. This components combine to be one system, so the system can work well function. Gondola was designed to clean the glass windows twice, but still has a weakness because the wiper motor can not clean the corners of the glass. Wind sensors can be ordered to stop gondola moment occurred when there is a average speed wind (angin sedang).